Combination therapy with toripalimab and lenvatinib in metastatic type 2 papillary renal cell carcinoma: a Case Report - Wang, Wende; Chen, Minna; Xue, Wenwu; Zeng, De (Frontiers in Immunology, 2025)
BackgroundType 2 papillary renal cell carcinoma (PRCC) is an aggressive subtype of renal cell carcinoma with a poor prognosis. Diagnosis is challenging, particularly when presenting as a metastatic lung mass. This report describes a case of metastatic type 2 PRCC treated with first-line toripalimab (anti-PD-1) and lenvatinib (multikinase inhibitor), highlighting sustained clinical benefit.Case presentationA 73-year-old man presented with cough, hemoptysis, and a large left lung mass initially misdiagnosed as primary lung cancer. Multidisciplinary re-evaluation, including immunohistochemistry (PAX8+, P504s+, also known as AMACR), confirmed metastatic type 2 PRCC. After 11 months of toripalimab (flat dose of 240 mg every 3 weeks) and lenvatinib (flat dose of 8 mg daily), serial imaging demonstrated partial response (PR) with regression of pulmonary metastases, lymphadenopathy, and obstructive pneumonia. No serious adverse events occurred.ConclusionsThis case underscores the potential efficacy and tolerability of toripalimab-lenvatinib combination therapy in metastatic type 2 PRCC. Further clinical trials are warranted to validate this approach.